2021
DOI: 10.1111/jan.15042
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of informal caregivers of people with dementia with nursing care in acute hospitals: A descriptive mixed‐methods study

Abstract: Aims To explore the experiences of informal caregivers of people with dementia with the hospitalization of their relative concerning patient care, interactions with nurses, caregivers’ situation and the acute hospital environment. Design Mixed‐methods design. Methods The data were collected using an online questionnaire among a panel of caregivers (n = 129), together with a focus group and individual interviews from February to November 2019. The data were triangulated and analysed using a conceptual framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Then, it is notable that asking about the patient's preferences has only been described in the preparation phase. This could explain the experiences of family caregivers and patients that their preferences are not considered (Bridges et al, 2020 ; Keuning‐Plantinga et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Then, it is notable that asking about the patient's preferences has only been described in the preparation phase. This could explain the experiences of family caregivers and patients that their preferences are not considered (Bridges et al, 2020 ; Keuning‐Plantinga et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…5 In acute hospitals, around half of family carers reported that their relatives were left with insufficient supervision during mealtimes. 6 People with severe dementia who have frequent care transitions, including to and from hospitals, are also more likely to receive artificial nutrition and hydration (ANH), including tube feeding 7,8 ; however, current evidence in severe dementia shows that tube feeding does not prolong a person's life, prevent aspiration, lead to better nutritional parameters, nor improve quality of life. 9 The 2005 Mental Capacity Act in England and Wales assumes someone has capacity to make decisions about their care and treatment, unless proven otherwise.…”
Section: Introductionmentioning
confidence: 99%
“…Basic support, such as for eating and drinking, can be suboptimal in acute hospitals 5 . In acute hospitals, around half of family carers reported that their relatives were left with insufficient supervision during mealtimes 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater presence of troublesome symptoms including neuropsychiatric symptoms and delirium, increases care partner distress. The pre-existing, chronic strain borne by care partners of persons with dementia is also compounded by anxiety about the comfort and safety of the patient during their hospital stay and the potential for increased care needs at discharge that they feel unprepared to meet (Keuning-Plantinga et al, 2021; Kuzmik et al, 2021; Shankar et al, 2014).…”
Section: Introductionmentioning
confidence: 99%